High Yield of Wax Ester Synthesized from Cetyl Alcohol and Octanoic Acid by Lipozyme RMIM and Novozym 435 - Chia-Hung Kuo; Hsin-Hung Chen; Jiann-Hwa Chen; Yung-Chuan Liu; Chwen-Jen Shieh (International Journal of Molecular Sciences, 2012)
Wax esters are long-chain esters that have been widely applied in premium lubricants, parting agents, antifoaming agents and cosmetics. In this study, the biocatalytic preparation of a specific wax ester, cetyl octanoate, is performed in n-hexane using two commercial immobilized lipases, i.e., Lipozyme® RMIM (Rhizomucor miehei) and Novozym® 435 (Candida antarctica). Response surface methodology (RSM) and 5-level-4-factor central composite rotatable design (CCRD) are employed to evaluate the effects of reaction time (1–5 h), reaction temperature (45–65 °C), substrate molar ratio (1–3:1), and enzyme amount (10%–50%) on the yield of cetyl octanoate. Using RSM to optimize the reaction, the maximum yields reached 94% and 98% using Lipozyme® RMIM and Novozym® 435, respectively. The optimum conditions for synthesis of cetyl octanoate by both lipases are established and compared. Novozym® 435 proves to be a more efficient biocatalyst than Lipozyme® RMIM.